Leczyme: A New Candidate Drug for Cancer Therapy. (23rd April 2014) - Tatsuta, Takeo; Sugawara, Shigeki; Takahashi, Kohta; Ogawa, Yukiko; Hosono, Masahiro; Nitta, Kazuo
Abstract : Sialic acid-binding lectin (SBL), isolated from oocytes of Rana catesbeiana, is leczyme and has both lectin and ribonuclease (RNase) activities. A remarkable antitumor effect of SBL has also been reported. SBL agglutinates various kinds of tumor cells but not normal cells. SBL agglutination activity is not affected by mono- or oligosaccharides. However, SBL-induced agglutination and antitumor effects are inhibited by sialomucin but not asialomucin. In addition, SBL has very little effect on sialidase-treated cells. SBL causes cancer-selective induction of apoptosis by multiple signaling pathways, which target RNA. Synergistic antitumor effects with other molecules, such as tumor necrosis factor-related apoptosis ligand (TRAIL) and interferon- γ (IFN- γ ), have been reported. Thus, SBL may be a novel candidate molecule for anticancer drug development. Sialoglycoconjugates on the tumor cell surface may be associated with lectin activity and antitumor effects of SBL. We review the properties of SBL, particularly its lectin, RNase, and antitumor activities, and comprehensively examine the potential application of SBL for clinical purposes.